The state of apoptosis factor system in mitochondria of skin and tumor cells in standard and stimulated growth of B16/F10 melanoma in female C57BL/6 mice - E. M. Frantsiyants; I. V. Neskubina; E. I. Surikova; A. I. Shikhlyarova; I. V. Kaplieva; L. A. Nemashkalova; L. K. Trepitaki (Исследования и практика в медицине, 2021)
Purpose of the study. Studying the dynamics of factors of apoptosis in mitochondria of skin and tumors cells in female mice with melanoma growth stimulated by chronic neurogenic pain. Material and methods. The study included female С57ВL/6 mice (n=56) with a model of chronic neurogenic pain (CNP) produced by the bilateral sciatic nerve ligation and with transplanted B16/F10 melanoma. After 1–3 weeks of the tumor growth, levels of cytochrome C, caspase‑9 (Bioscience, Austria), Bcl‑2 (Thermo Fisher Scientific, Austria), and AIF (RayBiotech, USA) were determined by ELISA, and levels of calcium (Са2+) were determined by the Arsenazo III method (Abris+, Russia) in mitochondria of tumors cells and skin not affected by the tumor growth. Results. In the CNP state, mitochondria of the skin cells showed a significant increase in Са2+ by 96.7 times, AIF by 1.4 times and Bcl‑2 by 5.9 times, while caspase‑9 decreased by 2.6 times, compared to the levels in intact mice. In the CNP‑stimulated melanoma growth, mitochondria of cells of the skin not affected by the tumor growth demonstrated a decrease in all studied indices, except caspase‑9 – its levels increased by 4.6 times after 3 weeks of the tumor growth. In mitochondria of the tumor cells within 1–3 weeks, levels of Са2+ decreased over time by 37.2–96.1 times, respectively, AIF by 49.4–2.0 times, Bcl‑2 by 3.0–1.5 times, cytochrome C by 15.3–8.8 times, and caspase‑9 increased by 1.7–4.4 times compared with the level in animals with pain. Conclusions. In general, the growth of melanoma stimulated by chronic pain and the standard melanoma growth were characterized by the opposite dynamics of levels of apoptosis factor both in mitochondria of skin cells and in mitochondria of tumor cells, with the exception of cytochrome C. Mitochondria of melanoma cells and of the unchanged skin have a similar tendency to change the levels of apoptosis factors, which may indicate their functioning in the conditions of the mitochondrial network at the level of one organ. Mitochondria of tumor cells provide the anti‑apoptotic state of the tumor itself and of the skin not affected by the malignant process, probably due to the stress state of the skin.